The Impact of ICT On Students' Academic Performance in Selected Secondary Schools in Western Division Rukungiri Municipality. - Agaba, Goddie (Kabale University, 2024)
This study investigated the impact of ICT on students' academic performance in selected secondary schools in Western Division, Rukungiri Municipality. The study also aimed to investigate the reiationship between the use of Information and Communication Technology (ICT) and academic performance among secondary school students in the Western Division-Rukungiri Municipality, Rukungiri District, identify the challenges faced in teaching and learning ICT and suggest ways of overcoming these challenges. The study was conducted using a sample of 52 respondents comprising 4 head teachers, 12 teachers, and 36 students. Data was collected using a structured questionnaire and analyzed using descriptive statistics. A questionnaire was used to collect data, and the results showed that the majority of respondents agreed that the use of ICT improves academic performance, helps understand difficult concepts, increases motivation to learn, and improves the overall learning experience. The lack of adequate ICT tools was identified as the biggest challenge faced by teachers and students in the study area. The provision of adequate ICT tools was the most suggested solution to the challenges faced in teaching and learning ICT in Western Division, Rukungiri Municipality. Based on the findings, recommendations were made to increase access to ICT tools, provide training in ICT skills, review the curriculum to incorporate f CT as a core subject and establish ICT resource centers. The study contributes to the literature on the effective integration of ICT in education and provides insights into policy and practice in Uganda.